Construcción de rodillos para el volteo de tanques elipticos en la empresa construcciones Ulloa Cia. Ltda - Ulloa Molina, Steven Oswaldo (2022)
This technological proposal was developed in Latacunga city- Cotopaxi province. Where there is a significant presence of the metal-mechanic industry; however, the company Construcciones Ulloa Cia. Ltda. that is a company that manufactures tanks, but is still having an old-fashioned way process, maintaining the traditional procedures and methods used since the company started. As a result, the processes obtained had become obsolete and causing delays in the production line, which has generated in several occasions unaccomplished the delivery time. Therefore, after an analysis realized through extensive dialogues with the owners of the company and seeking to establish solutions according to the benefits that the want to achieve, it was decided with the hand of Industrial engineering the construction of the rolling welding rotator for elliptical tanks for fuel transportation, in order to optimize the hands-on time by 50% and 70% only in the assembly process, in addition, the products can be obtained more efficiently and reduce manual labor in this specific process. Due this implementation, quality will be improved, and time and cost of production will reduce. Through the economic study, a positive return on investment is obtained, and a positive social impact could also be generated, involving local companies in the metal-mechanical industry to implement this product and contribute to the innovation in the local industry.